Inclusion of Lutein and Zeaxanthin in Standard or Omega-3 Fatty Acids Enriched Laying Hens Diets: Effects on Performance, Egg Quality Parameters, Fatty Acid Composition and Individual Carotenoids Concentration of Egg Yolk - Basmacıoğlu Malayoğlu, H; Aktaş, B; Karataş, F; Özdemir, P (Journal of the Hellenic Veterinary Medical Society, 2024)
The effects of lutein (L) and zeaxanthin (Z) inclusion to standard or omega-3 fatty acids enriched laying hens’ diets, on performance, egg quality parameters, fatty acids and individual carotenoids of egg yolk was investigated. The dietary treatments were designed as: standard (S) diet, 50 mg/kg L plus 50 mg/kg Z (S+L/Z (50+50)) or 100 mg/kg lutein plus 100 mg/kg zeaxanthin (S+L/Z (100+100)) added to S diet, Omega-3 fatty acids enriched (OM3) diet, 50 mg/kg lutein plus 50 mg/kg zeaxanthin (OM3+L/Z (50+50) or 100 mg/kg lutein plus 100 mg/kg zeaxanthin (OM3+L/Z (100+100)) added to OM3 diet. Hens with a mean live weight of 1525.88 ± 31.19 g were divided into six treatment groups. During the experimental period, there was not any mortality rate recorded. Dietary inclusion of L/Z (50+50 or 100+100) either in S or OM3 diets did not alter performance parameters. Eggs from hens fed enriched diet (OM3) significantly increased (P<0.05) the albumen index and Haugh unit. The type of dietary fat source (F), equal dose of L/Z or F×L/Z on egg yolk lutein, unknown carotenoids and total carotenoid concentration were found to be significant. However, the F on zeaxanthin concentration was not significant (P>0.05). The yolk color a* value was significantly increased by inclusion of L/Z (50+50 or 100+100) to diets (S or OM3) (P<0.05) and this was correlated with increased (P<0.05) concentration of individual carotenoids. The major changes in egg yolk fatty acid MUFA and PUFA composition occurred when laying hen fed with OM3 diet. Key words: Egg yolk, omega-3, carotenoids, lutein, zeaxanth